Remote monitoring and automated control system of the aquaponic system - Cárdenas Chambilla, Guiseppi Jordano (2025)
Aquaponics, a practice that combines aquaculture and hydroponics, offers a sustainable alternative for food production in areas with limited water resources, such as some regions of Peru. However, properly managing water parameters, which are essential to maintain the system's balance, remains a significant challenge. In this context, the study aimed to design and implement a remote monitoring system based on IoT to measure and control critical water parameters in an aquaponic fish farm in Tacna, Peru. The methodology included the development of a hardware infrastructure with pH, turbidity, temperature, and water level sensors, connected to an ESP32 LilyGO microcontroller with MQTT communication and equipped with a GSM/3G modem (SIM7000G). Additionally, software was designed for data collection, transmission, and cloud storage, enabling real-time monitoring and automated actions. The results showed an improvement in the stability of the monitored parameters, optimizing the efficiency of the aquaponic system and reducing human intervention. It is concluded that the implementation of IoT in aquaponics allows for precise, real-time control of water quality, contributing to a sustainable and efficient production process, reducing risks, and enhancing the system's resilience against environmental fluctuations.